A Novel Mobile Transactional Payment Banking Scheme - Obaid, Mahmoud Saleh Mahmoud (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
A novel real-time mobile payment (MOP) system that utilizes mobile phones together with interactive voice response technology (IVR) is proposed. The system consists of a communication network built upon existing banking infrastructures, thus minimizing the cost of adoption by banks. A sender or receiver communicates only with his/her bank, using a regular mobile phone, and banks talk to each other through a central authority, which acts as a broker. The communication of each component with other components in the system is clearly specified. Provision is made for the security of the whole system, making use of existing security arrangements between each participating bank and its customers, as well as established security practices of the banking industry. Rollbacks of transactions are also available. Our scheme aims to achieve a high level of security without sacrificing efficiency, have a reliable infrastructure, minimize the overheads on all stakeholders and result in time savings in implementation and marketing. Through our scheme, all bank services involving transfer of funds between participants will become readily available anytime and anywhere, regardless of the availability of Internet or smart phones. For example, a user of the system will be able to pay for purchases, transfer money, track payments, and receive money in real time, alleviating the need to carry cash or credit cards. Keywords: Communication network, real-time mobile payment, M-commerce, Interactive Voice Response, protocol, transaction, security

ÖZ: İnteraktif Ses Teknolojisi (IVR) ile birlikte mobil telefonları kullanan, yeni ve gerçek zamanlı bir mobil ödeme sistemi (MOP) öneriyoruz. Sistem, varolan bankacılık altyapısı üstüne kurulu olmasından dolayı bankaların sisteme dahil olmasının maliyetini azaltan bir iletişim ağından oluşur. Gönderici veya alıcı sadece yalın bir mobil telefon kullanarak kendi bankası ile iletişim kurar, ve bankalar da bir aracı görevi gören merkezi otorite vasıtası ile haberleşirler. Sistemdeki tüm parçaların diğer parçalarla haberleşmesi açıkça belirlenmiştir. Tüm sistemin güvenliği, müşteriler ile bankaları arasında hali hazırda var olan güvenlik önlemleri, ve bankacılık sektöründe kullanımda olan güvenlik uygulamaları üzerine inşa edilmiştir. Hareketlerin geridönüşü de sağlanmıştır. Yöntemimiz, verimlilikten ödün vermeden yüksek düzeyde güvenlik sağlamayı, güvenli bir altyapıya sahip olmayı, tüm paydaşların mali yükünü en aza indirmeyi, ve hem implementasyonda, hem de pazarlamada zaman kazandırmayı hedefler. Yöntemimiz aracılığı ile, fon aktarımı içeren tüm bankacılık hizmetleri, İnternet ve akıllı telefonlar olmadan, her zaman ve her yerde kolayca gerçekleştirilebilecektir. Örneğin, bir sistem kullanıcısı, para veya kredi kartı taşımasına gerek kalmadan, gerçek zamanlı olarak alış-verişleri için ödeme yapabilecek, para aktarımı yapabilecek, ödemelerini takip edebilecek, ve ödeme alabilecektir. Anahtar Kelimeler: İletişim ağı, gerçek zamanlı mobil ödeme, M-ticaret, interaktif ses teknolojisi, protokol, hareket.
Doctor of Philosophy in Computer Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2020. Supervisor: Assoc. Prof. Dr. Zeki Bayram.
Keywords: Computer Engineering; Electronic Commerce; Communication network; real-time mobile payment; M-commerce; Interactive Voice Response; protocol; transaction; security